2015
DOI: 10.1093/fampra/cmv003
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the burden of minor ailment consultations in general practices and emergency departments through retrospective review of routine data in North East Scotland

Abstract: Background.Minor ailment attendances in general practices and emergency departments (EDs) place significant burden on health care resources.Objectives.To estimate the prevalence and type of minor ailment consultations for adults in general practice and ED that could be managed in a community pharmacy.Methods.Retrospective review of routine data from general practices (n = 2) and one ED in North East Scotland. Two independent consensus panels assessed each consultation summary to determine whether it represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
91
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 14 publications
1
91
0
5
Order By: Relevance
“…It has been found that 18·5% of consultations in high‐cost settings, such as emergency departments (ED) and primary care clinics (PCC), involve conditions that are in fact manageable without medical intervention (Fielding et al . ). Due to the global and ever‐increasing problem of antimicrobial resistance, voices have called for decreased medical treatment of conditions that are self‐limiting to their nature (Mölstad et al .…”
Section: Introductionmentioning
confidence: 97%
“…It has been found that 18·5% of consultations in high‐cost settings, such as emergency departments (ED) and primary care clinics (PCC), involve conditions that are in fact manageable without medical intervention (Fielding et al . ). Due to the global and ever‐increasing problem of antimicrobial resistance, voices have called for decreased medical treatment of conditions that are self‐limiting to their nature (Mölstad et al .…”
Section: Introductionmentioning
confidence: 97%
“…ED presentations are increasing worldwide at a consistent rate with overcrowding, access block and prolonged waiting times for patients accessing emergency care . Much has been written about the inappropriate use of EDs by low acuity or general practice‐type (GP‐type) patients, with an assumption that these patients are causing overcrowding in EDs …”
Section: Introductionmentioning
confidence: 99%
“…1 Most people around the world do not seek formal care for these illnesses, but when that path is chosen, it can have a significant impact on a health care system. [2][3][4][5][6][7] The situation is similar in Canada, where medical care for socalled minor ailments is costly. Over-the-counter (OTC) medicine industry executives claim that one in seven Canadians with minor ailments visit a physician.…”
Section: Introductionmentioning
confidence: 99%